Pocket-book of useful formulae and memoranda for civil and mechanical engineers - Molesworth, Guilford L. Sir, 1828-1925; Molesworth, Egbert Brieges (ICE Publishing, 2011)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present.
Includes index.
Keywords: Civil engineering -- Handbooks, manuals, etc.; Mechanical engineering -- Handbooks, manuals, etc.; elektronické knihy; electronic books